Análisis de la calidad de energía en los sistemas de bombeo Electrosumergible y horizontal alimentados con PWM y 6-step de la marca BH - Segovia Segovia, Diego Ramón (2023)
Much of the development and industrial application of power converters is due to the progress experienced in the generation of any desired voltage waveform. The appearance of modulation techniques, together with the possibility of implementing them in modern microprocessors or configurable electronic devices, has favored the use of frequency inverters and their development in the hydrocarbon sector for Artificial Lift applications implemented in the processes. production and transportation of oil through electrosubmersible and horizontal pumping systems. Different frequency inverter topologies and modulation methods allow a power converter to impose any voltage waveform on the load to which it is connected. In this work, the 2 methods implemented in the frequency variators of the B.H. brand are analyzed and compared. through PWM and 6-STEP modulation techniques, using an experimental methodology for measuring the quality of electrical power supplied to the load, simulation tools based on Matlab - Simulink and calculation of harmonic power of the load in the studied pumping systems. The objective is to propose a comparative analysis, which allows understanding the operation of each modulation technique, observing the advantages and disadvantages of the different methods presented.